1975
DOI: 10.1073/pnas.72.12.4948
|View full text |Cite
|
Sign up to set email alerts
|

13C-nuclear magnetic resonance study of [85% 13C-enriched proline]thyrotropin releasing factor: 13C-13C vicinal coupling constants and conformation of the proline residue.

Abstract: To understand fully interactions between peptides and cellular receptors, peptide side chain conformation must be defined. In many cases the complexity of proton nuclear magnetic resonance (NMR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 41 publications
(32 reference statements)
2
11
0
Order By: Relevance
“…In proline, the 1 J CαC coupling senses the cis/trans isomeric state of the preceding Xaa-Pro peptide bond, with 1 J CαC decreased by 1.4 Hz in the cis state. [43] In DFPase, the peptide link Ala140-Pro141 is cis configured, and so are Asp90-Pro91 and Pro106-Pro107 in Xylanase, and Tyr38-Pro39 and Ser54-Pro55 in RNase T1. [102] Not all proline 1 J coupling constants were available in our dataset, lacking especially some values of 1 J CαN (Table S3).…”
Section: Jmentioning
confidence: 99%
See 1 more Smart Citation
“…In proline, the 1 J CαC coupling senses the cis/trans isomeric state of the preceding Xaa-Pro peptide bond, with 1 J CαC decreased by 1.4 Hz in the cis state. [43] In DFPase, the peptide link Ala140-Pro141 is cis configured, and so are Asp90-Pro91 and Pro106-Pro107 in Xylanase, and Tyr38-Pro39 and Ser54-Pro55 in RNase T1. [102] Not all proline 1 J coupling constants were available in our dataset, lacking especially some values of 1 J CαN (Table S3).…”
Section: Jmentioning
confidence: 99%
“…Depending markedly on pH in terminal polypeptide residues and free amino acids, [22,23] the 1 J CαC coupling constant is largely pH independent in intrachain residues, averaging 52.8 ± 1.8 Hz. [42,43] The 109 values of 1 in flavodoxin average 52.4 ± 1.9 Hz, essentially uncorrelated with secondary structure or hydrogen-bonding patterns. [44] The 30 values of 1 J CαC reported for troponin C average 53.0 ± 0.7 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these values correlate with the mean of the chemical shifts of the coupled atoms C', C", and C", C@, which are dif- At the same time, 4.1 Hz is found for 3 J~' 1 ca and no 3Jc,.c1 and 3Jc,.c~ are observed in the trans conformer, similar to other proline peptides where the pyrrolidine ring exhibits mainly the type A puckering. 17,20,23 On the other hand, it has been shown that when the difference between ' J H~~H P and 3 J~c y~~ reaches its maximum ( " J H~H P -0), the H(Y resonance is most strongly shifted downfield (4.7 ppm).57 Thus the proline Ha chemical shifts and the " J H~H~? and : ' J H~+~ couplings are both influenced by steric factors affecting the geometry of the proline residue.…”
Section: Proline Ring Conformationmentioning
confidence: 94%
“…Photolyses were carried out using a 450 W Hsnovia medium pressure Hg lamp. Thin layer chromatography was performed on Whatman precoated silica gel plates using the following solvent systems: (I) hexanesether (2 : 1); (11) Polypropylene 74p mesh packets (50 x 50 mm) were prepared as previously HF cleavage of the peptide from the resin was effected using a HF reactor, type I apparatus (Protein Research Foundation, Osaka, Japan). Optical rotations were measured using a Perkin-Elmer Model 141 polarimeter.…”
Section: Met Hodsmentioning
confidence: 99%